2015
DOI: 10.1007/s13187-015-0859-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Culturally Tailored Education to Promote Breast and Cervical Cancer Screening Among Chinese-Australian Women

Abstract: Our study supports that educational programs which use culturally sensitive and linguistically appropriate strategies are effective in improving both knowledge of breast and cervical cancer and awareness of their early detection practices among Chinese-Australian women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Previous literature has shown that culturally tailored community interventions have been effective in increasing cancerscreening rates, as well as knowledge, perceived risk of cancer and benefits of cancer screening among other racial minority populations (Percac-Lima et al 2009) (Gotay et al 2000) (Wang et al 2008) (Kwok and Lim 2016). In each of the interventions, the authors surmise that the culturally tailored messages and understanding of the social context of the participants' lives increased the ability to recruit and retain participants.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has shown that culturally tailored community interventions have been effective in increasing cancerscreening rates, as well as knowledge, perceived risk of cancer and benefits of cancer screening among other racial minority populations (Percac-Lima et al 2009) (Gotay et al 2000) (Wang et al 2008) (Kwok and Lim 2016). In each of the interventions, the authors surmise that the culturally tailored messages and understanding of the social context of the participants' lives increased the ability to recruit and retain participants.…”
Section: Discussionmentioning
confidence: 99%
“…The pap smear method was aimed at women aged 18-70 years. Pap smear tests were carried out regularly, proven effective in reducing mortality from cervical cancer (Kwok & Lim, 2016).…”
Section: Cervical Cancer Screening Methodsmentioning
confidence: 99%
“…Other studies using leaflets and online were less effective in increasing cervical screening uptake compared to the sampling method itself (Kitchener et al, 2018). There were also studies that use effective cultural and language approach strategies to increase women's knowledge and awareness about breast cancer screening and cervical cancer succeed in increasing the intention and participation in screening mammographs and pap smear tests (Kwok & Lim, 2016).…”
Section: Interventions To Increase Cervical Cancer Screening Participationmentioning
confidence: 99%
“…These issues are explored by Tung, Granner, Lu, & Qiu (). The need for strategies which are culturally sensitive and linguistically appropriate is often emphasised—existing models of behaviour change often need to be adapted for use in ethnic subgroups (Kwok & Lim, ). Davis, Oaten, Occhipinti, Chambers, and Stevenson () examine barriers to colorectal cancer screening—there are well‐established differential rates of screening uptake, and factors including age, sex, socio‐economic status, ethnic subgroups, attitudes, emotions and beliefs all play a significant role (Honein‐AbouHaidar et al., ; Lo, Waller, Vrinten, Kobayashi, & von Wagner, ).…”
mentioning
confidence: 99%